Usefulness of red blood cell size factor (RSf) in screening genetic variants of alpha thalassaemia thalassaemia trait regardless of iron status - Idris, Nur Juliana; Idris, Faridah; Seman, Zainina; Nik Mustapha, Nik Hafidzah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Screening for alpha (α) thalassaemia trait (TT) is challenging especially in the presence of iron deficiency (ID). Red blood cell size factor (RSf) is a parameter introduced by Beckman Coulter capable of detecting acute and chronic changes to cellular haemoglobin status and iron supply. The research aimed to investigate the clinical usefulness of RSf as screening parameter for α TT and the effect of concomitant ID to RSf mean values (m.v) among respondents with α TT. Methods: A cross-sectional retrospective laboratory analysis involved 55 respondents’ data selected from January 2014 to December 2015 in Pathology Department, Hospital Tuanku Ja’afar Seremban, Negeri Sembilan. The significant difference at p <0.05 in the RSf m.v. among respondents with α0 TT, α+ TT, and ID groups and the effect concomitant ID to RSf m.v. were determined using statistical test, one-way analysis of variance (ANOVA). Results: Significant differences were detected in RSf m.v. i) between α0 TT, α+ TT and ID, F (2, 52) = 18.99, p=0.001. ii) between α TT without ID, α TT with ID and ID cohorts for both a) α0 TT [F (2, 33) = 23.77, p=0.001) and b) α+ TT [F (2, 28) = 5.37, p=0.011]. iii) between α TT and ID group regardless of the presence of ID for both a) α0 TT and b) α+ TT. Conclusion: RSf is a potential screening parameter in evaluating patients with hypochromic microcytosis in identifying possible cases of alpha TT regardless of iron status.